2D-Hydrodynamic Energy Model Including Avalanche Breakdown Phenomenon for Power Field Effect Transistors. Issue 1 (2001) - Rousseau, M.; De Jaeger, J. C.
Abstract : A 2D-Hydrodynamic model is carried out to predict the breakdown voltage of microwave field effect transistors. The model is based on the conservation equations inferred from Boltzmann's transport equation, coupled with Poisson's equation. In order to take into account the channel avalanche breakdown, the charge conservation equations for electrons and holes are considered and a generation term is introduced. The set of equations is solved using finite difference and different computational methods have been tested to save computing time. The model allows us to obtain accurate predictions for power transistors considering a usual gate recess. Results are performed for pseudomorphic ALGaAs/InGaAs/GaAs HEMTs.